2010
DOI: 10.1186/1471-2407-10-494
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-4 is a putative tumour-suppressor gene in colorectal cancer that exhibits age-related methylation

Abstract: BackgroundThrombospondin-4 (THBS4) is a member of the extracellular calcium-binding protein family and is involved in cell adhesion and migration. The aim of this study was to evaluate the potential role of deregulation of THBS4 expression in colorectal carcinogenesis. Of particular interest was the possible silencing of expression by methylation of the CpG island in the gene promoter.MethodsFifty-five sporadic colorectal tumours stratified for the CpG Island Methylator Phenotype (CIMP) were studied. Immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 23 publications
2
36
1
Order By: Relevance
“…Some reports have shown TSP4 protein expression may facilitate invasion of tumor cells in breast cancer and hepatocellular carcinoma [12,25]. In contrast, another study reported that TSP4 may act as a tumor suppressor gene in colorectal cancer [26]. There are several possible reasons for the discrepancies between these findings: First, tumor progression is a dynamic, precisely regulated, multistep process, and TSP4 is an inducible marker that can be upregulatedor downregulated over time [27].…”
Section: Discussioncontrasting
confidence: 42%
“…Some reports have shown TSP4 protein expression may facilitate invasion of tumor cells in breast cancer and hepatocellular carcinoma [12,25]. In contrast, another study reported that TSP4 may act as a tumor suppressor gene in colorectal cancer [26]. There are several possible reasons for the discrepancies between these findings: First, tumor progression is a dynamic, precisely regulated, multistep process, and TSP4 is an inducible marker that can be upregulatedor downregulated over time [27].…”
Section: Discussioncontrasting
confidence: 42%
“…Once induced in select tissues, Thbs protein expression can be observed directly within cells or between cells in the extracellular space (Chen et al, 2000; Sodersten et al, 2007; Veliceasa et al, 2007; Greco et al, 2010). We observed prominent Thbs4 protein localization within the ER/SR compartment of adult cardiomyocytes of the heart, with some mild accumulation in the extracellular space or ECM.…”
Section: Discussionmentioning
confidence: 99%
“…We observed prominent Thbs4 protein localization within the ER/SR compartment of adult cardiomyocytes of the heart, with some mild accumulation in the extracellular space or ECM. Indeed, while Thbs’ are generally secreted, examples of their intracellular retention in the ER or vesicles have been reported (Chen et al, 2000; Sodersten et al, 2007; Veliceasa et al, 2007; Hauser et al, 1995; Greco et al, 2010). Thbs’ are assembled into trimers (Thbs1 and 2) or pentamers (Thbs3, 4, and 5) in the ER, and Thbs1 was shown to be part of a complex with PDI, BiP, p72 and Grp94, and to reside in the ER compartment for up to 30 minutes before presumably shuttling to the Golgi for gylcosylation (Prabakaran et al, 1996; Kuznetsov, 1997; Hecht et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…FGF-BP increases tumorigenicity and is highly expressed in colon carcinoma [64] TGM2 (transglutaminase 2) Elevated expression is found in compact spheroid formation by ovarian cancer cells [65] C. Transcripts down-regulated by resveratrol and up-regulated by IL-6 EFNA1 (Ephrin A1) It binds to the Eph A2 tyrosine kinase receptor, which drives migration and invasion of colorectal cancers. Its mRNA expression correlates with poor prognosis in hepatocarcinoma and colorectal cancers [41,66,67] THBS4 (thrombospondin 4) It is a stromal protein involved in cellular migration, adhesion, and attachment that has been shown to play a role in metastatic progression of lung, breast, and colorectal cancers [68][69][70] SGK1 (serum and glucocorticoid regulated Kinase 1)…”
Section: Il-6 and Resveratrol Modulate The Transcriptome And The Micrmentioning
confidence: 99%